Peran Guru di Sekolah dan Masyarakat - Muhammad Yasin; Rosaliana, Rosaliana; Sevia Rahayu Nur Habibah (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
The existence of a teacher plays an important role in the community environment both at school and in society. Teachers are required to have exemplary personality and behavior in social life in society. The position of a teacher demands to be professional in educating and behaving not only related to his duties in the learning process but also his duties in society. The research objective is to find out how the teacher's role is in schools and society and the obstacles to the teacher's role. The focus of this research is what is the role of the teacher in schools and the community and what are the obstacles encountered in carrying out the role of the teacher in schools and the community. The method used by researchers is a qualitative research method with a descriptive type that collects data using interviews, journals, and field observations. The results of this study that 1). The role of the teacher both at school and in the community is very important as a factor in achieving the goal of quality education. 2). The inhibiting factors in carrying out the teacher's role cannot hinder their role as a teacher but make it a challenge faced by the teacher.